Pengaruh Kualitas Sumber daya Manusia, Korupsi dan Ketimpangan Pendapatan Terhadap Kemiskinan Di Indonesia - Muhammad Abram; Yeniwati Yeniwati (Universitas Negeri Padang, 2021)
This study explains the extent of the influence between the Quality of Human Resources, Corruption, Income Inequality on Poverty in Indonesia. This study combines cross section data in 33 provinces with time series from 2011-2019, using the Panel Regression method with a Fixed Effect model selection test. ) 1) Quality of Human Resources has a negative and significant effect on Poverty in Indonesia, 2) Corruption has a positive and insignificant effect on poverty in Indonesia, (3) income inequality has a positive and insignificant effect on poverty in Indonesia.